The Relationship Between CDC Personnel Subjective Socioeconomic Status and Turnover Intention: A Combined Model of Moderation and Mediation - Shan, Ying; Liu, Guangwen; Zhou, Changqiang; Li, Shixue (Frontiers in Psychiatry, 2022)
A stable and motivated CDC workforce is critical for Chinese public health system improvement in the post-pandemic period of COVID-19. Meanwhile, the lack of career development prospects, low income, low status and the widespread and increasingly serious job burnout of employees CDC staff is a complex and difficult problem for the government. Therefore, this study explored the relationship between CDC personnel subjective socioeconomic status and turnover intention using a sample of 2502 grass-roots CDC personnel who were administered with a subjective socioeconomic status scale, turnover intention scale, job burnout scale, and payment questionnaire. The results showed that: (1) subjective socioeconomic status had a significant predictive effect on job burnout and turnover intention; (2) all three dimensions of job burnout played a mediating role in the relationship between subjective socioeconomic status and turnover intention;(3) expected salary change played a moderating role between subjective socioeconomic status and turnover intention. The effect was stronger for workers with low expected salary change, which means due to the multidimensional comparative and complex mechanism of salary change, which had limited effect on turnover intention. These findings provide a basis for the relationship between turnover intention and socioeconomic status of grass-roots CDC personnel, and also provide ideas for reducing job burnout and staff turnover.